Strengthening The Character of Global Diversity Through Child-friendly School Programs by Utilizing 5S (Smile, Greetings, Greetings, Politeness, Courtesy) in the Regional Coordinator for Education, South Cilacap District - Ayu Pratama (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This study aims to analyze the strengthening of Global Diversity through the Child-friendly School Program utilizing the 5S culture (Smile, Greeting, Salutation, Politeness, Courtesy) at SD KorwilBiddik South Cilacap, and to describe the supporting and inhibiting factors of learning to strengthen Global Diversity through this program in the South CilacapBiddik Regional Council. Using a descriptive qualitative research approach, the study focuses on students, teachers, and elementary school principals in both public and private schools in the region, particularly on the implementation of child-friendly schools through the 5S culture to enhance the character of global diversity among students. The findings reveal that schools in the South CilacapBiddik Regional Council have effectively implemented child-friendly school policies and integrated the 5S program into daily school activities. The supporting factors include school policies, teachers, the school environment, parents, supportive subject matter, and adequate facilities and infrastructure. However, there are inhibiting factors such as inconsistencies among school residents in implementing the program, the diversity of student characteristics, and differing habits of students at school and at home. Despite these challenges, the 5S program has been well-implemented daily, fostering respectful and friendly behavior towards teachers and peers, thereby enhancing students' global diversity character.